2022
DOI: 10.1093/ijpp/riac058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacists’ perceptions of the barriers and facilitators to the implementation of paediatric clinical pharmacy services in Hong Kong

Abstract: Objectives To identify barriers and facilitators that influenced the implementation of paediatric clinical pharmacy service (CPS) in Hong Kong’s public hospitals from clinical pharmacists’ perspective. Methods A qualitative study based on semi-structured interviews of clinical pharmacists who practiced in paediatrics in public hospitals in Hong Kong. Interview schedule was designed based on determined themes identified in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The factors that were identi ed in this study are coherent with a parallel study conducted with clinical pharmacists as part of a series of the PI's doctoral portfolio, thus re ecting the consistency and reliability of the ndings [13].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The factors that were identi ed in this study are coherent with a parallel study conducted with clinical pharmacists as part of a series of the PI's doctoral portfolio, thus re ecting the consistency and reliability of the ndings [13].…”
Section: Discussionsupporting
confidence: 70%
“…The methodology of this study was informed by the earlier publication from the same research team with different target participants [13]. Semi-structured interviews (SSIs) were used for data collection, with the interview guide developed based on factors identi ed in paediatric CPSs [14].…”
Section: Methodsmentioning
confidence: 99%
“…[9] The methodology of this study was informed by an earlier publication from the same research team with clinical pharmacists. [10] Semi-structured interviews (SSIs) were used for data collection, with the interview guide developed from the themes and subthemes identified in systematic reviews identifying factors in both adult and paediatric CPSs (see Supplemental Material). [11,12] As all researchers agreed that no amendments were required after pilot testing the guide with three participants and therefore, the data were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The findings from this study of 32 respondents (clinical pharmacists) identified five primary obstacles hindering service implementation in the pediatric clinical pharmacy. [6] These barriers included administrative challenges, facility environment constraints, insufficient service penetration into the healthcare system, weak governance and waning professionalism, and lack of partnership with research institutions. [6] According to the study, remedies for the pediatric service implementation consisted of self-efficacy from clinical pharmacists and pharmacy management team, confidence, and trust from healthcare professionals.…”
Section: Literature Reviewmentioning
confidence: 99%